Early-onset versus late-onset fetal cerebral ventriculomegaly: Sonographic characteristics and neonatal outcomes - Dayanan, Ruken; Filiz, Ahmet Arif; Ayas Özkan, Merve; Duygulu Bulan, Dilara; Ayhan, Hatice; Bakan, Ecem; Karabay, Gülşan; Çelen, Şevki (The European Research Journal, 2025)
Objectives: This study aimed to compare the prenatal ultrasound characteristics, pregnancy outcomes, and neonatal prognosis of early- and late-onset fetal ventriculomegaly (VM). Methods: A retrospective analysis was conducted on 102 pregnant women diagnosed with fetal VM, categorized into early-onset (≤24 weeks) and late-onset (>24 weeks) groups. Maternal characteristics, ventricular dimensions, associated anomalies, pregnancy outcomes, and neonatal parameters were compared between the groups. Results: Early-onset VM was significantly associated with progressive ventricular enlargement, bilateral involvement, and a higher prevalence of additional anomalies detected via ultrasonography (70.4% vs. 29.2%, P<0.001) and Magnetic resonance imaging (MRI) (35.4% vs. 16.7%, P=0.030). Prenatal ultrasound findings differed significantly between the groups; early-onset VM cases more frequently exhibited bilateral (72.2% vs. 39.6%, P=0.002) and asymmetric (46.3% vs. 31.2%, P=0.037) ventricular enlargement, while late-onset VM was more commonly isolated (70.8% vs. 29.6%, P<0.001) and unilateral (60.4% vs. 27.8%). Live birth rates were lower (55.6% vs. 85.4%, P=0.001), pregnancy termination rates were higher (44.4% vs. 14.6%, P=0.001) and chromosomal abnormalities were higher (16.7% vs. 8.3%, P=0.246) in early-onset cases. Additionally, Apgar scores at 1 and 5 minutes were significantly lower in the early-onset group (P=0.028 and P=0.042, respectively). Conclusions: Early-onset VM is more frequently associated with ventricular progression and structural anomalies, leading to poorer pregnancy and neonatal outcomes. These findings highlight the importance of close prenatal monitoring, including detailed ultrasound, fetal MRI, and genetic evaluation, to guide clinical management and parental counseling. Future studies with long-term neurodevelopmental follow-up are needed to further refine risk stratification and optimize patient care.